A combinatorial approach to enhance the biocompatibility and heating efficiency of magnetic hyperthermia- Serum Albumin conjugated ferrimagneticmagnetite nanoparticles. Issue 3 (2016) - Kalidasan, Viveka; Liu, Xiaoli; Ding, Jun; Dasgupta, Ananya; Sajikumar, Sreedharan
ABSTRACT: Magnetic hyperthermia is a non-invasive cancer treatment method which is used synergistically with the current cancer treatments. Improved biocompatibility and enhanced heating characteristics are the pressing challenges to be addressed in magnetic hyperthermia. Through a novel combinatorial approach, we have attempted to address both the challenges. Ferrimagneticmagnetite nanoparticles (FMNPs)of size 50 nm were synthesized by thermal decomposition method and were converted to hydrophilic phase by 3-Aminopropyltrimethoxysilane (APTMS). Serum Albumin (SA) from rat was conjugated over the APTMS-FMNPs to convert to biocompatible phase. The preliminary haemolysis experiments show that SA-FMNPs are non-haemolytic (1.2 % haemolysis). It is observed from the magnetic heating experiments that due to better colloidal stability, the Specific Absorption Rate value of the SA-FMNPs are higher (2100 W/g) than the FMNPs without SA (1400 W/g). Thus we report here that SA conjugation over FMNPs (with a high saturation magnetization of 75 emu/g) provides a novel combinatorial approach to enhance both the biocompatibility and the SAR value for magnetic hyperthermia.